Smart Bicycle Sharing System for Non-Commercial Purposes using Time-based One-Time Password Algorithm - Humaira Abu Backer Sidek, Husna; Amri Jamal, Azrul; Makhtar, Mokhairi; Abdullah Fadzli, Syed (International Journal of Engineering and Technology, 2018)
Bicycle sharing systems have been accepted openly by the public. Many developed countries prepared some kind of bicycle sharing system in order to advocate exercising and promotes healthy living. Nevertheless, these systems are usually for commercial purposes and required the user to pay some amount of money to use the service. This paper discusses regarding smart bicycle sharing system designed for non-commercial use, such as in universities, schools, or small villages where the bicycle sharing service are to be given out to users without a fee. At the same time, the whereabouts and availability of the bicycles should be managed carefully in order to avoid losing the bicycles. Several one-time password algorithms have been studied and the most suitable algorithm has been used to generate a 6-digit code in order to unlock bicycles from its bicycle stations. The system is designed to be as easy to use as possible, and with an acceptable amount of security.Â Â